Composition and structure of coal organic mass. 2. Kinetic models of metamorphism - Barsky, Vadim; Vlasov, Gennady; Rudnitsky, Andriy (Publishing House of Lviv Polytechnic National University, 2011)
Regularities of changes in solid fuel elemental сomposition during metamorphism have been investigated. A mathematical model describing these regularities as functions of Cdaf has been developed. Experimental data of artificial coalification confirm that it is an experimental model of natural metamorphism. Досліджено закономірності зміни в ході метаморфізму елементного складу твердого палива та побудовано математичну модель, що описує ці закономірності як функції від Сdaf. За допомогою експериментальних даних штучної вуглефікації показано, що вона є експериментальною моделлю природного метаморфізму.
Про склад і будову органічної маси вугілля. 2. про кінетичні моделі метаморфізму
Keywords: metamorphism; coal; chemical structure; метаморфізм; вугілля; хімічна будова